Exposure to Increased Environmental Complexity during Rearing Reduces Fearfulness and Increases Use of Three-Dimensional Space in Laying Hens (Gallus gallus domesticus) - Brantsæter, Margrethe; Nordgreen, Janicke; Rodenburg, T. Bas; Tahamtani, Fernanda M.; Popova, Anastasija; Janczak, Andrew M. (Frontiers in Veterinary Science, 2016)
The complexity of the rearing environment is important for behavioral development and fearfulness. The aim of this study was to test the hypothesis that laying hens reared in a complex aviary system with exposure to mild intermittent stressors, would be less fearful, less sensitive to stress, and would use elevated areas of the pen more often as adults than hens reared in a barren cage environment. Laying hens (N = 160) were housed in the same rearing house; half of the birds (n = 80) in an aviary and the other half (n = 80) in cages. At 16 weeks of age, the birds were transported to the experimental facilities. Their behavior was recorded at 19 and 23 weeks of age and analyzed by ANOVA on individual scores for a fearfulness-related principal component generated using principal component analysis (PCA). The results indicate that aviary-reared birds had lower levels of fearfulness, compared with cage-reared birds both at 19 weeks and at 23 weeks of age. When comparing the response induced by initial exposure to a novel object at 19 and 23 weeks of age, more aviary-reared birds tended to fly up at 19 weeks compared to the cage-reared birds, indicating a tendency towards a more active behavioral response in the aviary- than in cage-reared birds. There was no difference between treatments in the flight response at 23 weeks. The groups did not differ in defecation frequency or the concentration of fecal corticosterone metabolites at either age. At 19 weeks, observation of the spatial distribution in the home pens indicated that more aviary-reared birds spent time on the low perch, the elevated platform and upper perch compared to the cage-reared birds. However, at 23 weeks of age, these differences were no longer detected. The results of this study support the hypothesis that increased environmental complexity during rearing reduces fearfulness of adult laying hens.